Soviet Communal Living - Messana, P. author. aut Link
XVI, 168 p. 1 illus.
Keywords: This book brings together fascinating testimonies from thirty inhabitants of the 'Kommunalka,' the communal apartments that were the norm in housing in the cities of Russia during the whole history of the Soviet Union.